Analysis of Structural Transformation in Agricultural Sector in Indonesia - Aziz, Abdul; -, Ragimun (Journal of Economics and Behavioral Studies, 2017)
Indonesia’s economy is currently undergoing a sharp shift of structural transformation. This is evident from the change in the proportion of major sectoral contributions to GDP in Indonesia. The agricultural sector in 2000 accounted for 15.60 percent of the national GDP. This sector is experiencing a gradual downward trend in 2015 which only contributes 12.18 percent. On the other hand there is an increasing contribution to GDP for the trade sector from 16.15 percent in 2000 to 18.06 percent by 2015. The study aims to identify the structural transformation of the agricultural sector in Indonesia, identify fiscal policy, appropriate development programs and can be implemented. The research methodology used is to explore the theory and implementation of several other countries by using SWOT analysis. The results of this research analysis found that the shift of structural transformation in the agricultural sector has the potential to cause negative impacts on several macroeconomic indicators such as GDP per capita persector and workforce of the sector. Therefore, there are several fiscal instruments that can be recommended, among others through credit programs such as Credit for Business Programme, subsidies and agricultural credit. Moreover, it can be done through agricultural insurance schemes and programs to increase infrastructure spending in agriculture so that the structural transformation is expected to keep Indonesia’s economic growth more inclusive.